Temporal trend and subgroup disparities in the prevalence and treatment of those who screen positive for depression in China: A population-based study - Chen, Shanquan; Wang, Yuqi (Frontiers in Psychiatry, 2023)
Background In China, improving mental health has been far behind its accomplishments for other diseases. With depression as one of the most prevalent mental disorders, the aim of this study was to evaluate temporal trends in the prevalence and treatment of those who screen positive for depression in China, by age, gender, and province Methods We used data from three nationally representative sample surveys: the China Health and Retirement Longitudinal Study, the China Family Panel Studies, and the Chinese Longitudinal Healthy Longevity Survey. Depression was judged by the Centre for Epidemiologic Studies Depression Scale. Access to treatment was judged by two items: if respondents received any treatment like anti-depressants, or if respondents received counselling from a mental health professional. Survey-specific weighted regressions were fitted to estimate the temporal trend and subgroup disparities, and then pooled by meta-analysis. Results 168,887 respondents were investigated. The overall prevalence of China populations who screen positive for depression was 25.7% (95%CI 25.2-26.2) during 2016-2018, decreased from 32.2% (95%CI 31.6-32.8) during 2011-2012. The overall proportion of those who received any needed treatment or counselling from a mental health professional increased from 2011 (0.5%, 95%CI 0.4-0.7) to 2018 (0.9%, 95%CI 0.7-1.2). Above results by age, gender, and province were also reported. Conclusion The prevalence of those who screen positive for depression had decreased in China, but only tiny improvements were made in accessibility to mental health care. Corresponding disparities were identified in age, gender, and province.